2022
DOI: 10.1002/acm2.13764
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive quality assurance procedure for 4D CT commissioning and periodic QA

Abstract: Purpose The 4D computed tomography (CT) simulation is an essential procedure for tumors exhibiting breathing‐induced motion. However, to date there are no established guidelines to assess the characteristics of existing systems and to describe meaningful performance. We propose a commissioning quality assurance (QA) protocol consisting of measurements and acquisitions that assess the mechanical and computational operation for 4D CT with both phase and amplitude‐based reconstructions, for regular and irregular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Two separate groups also recently published a detailed overview of their QA workflow for 4DCT commissioning and periodic QA. In the workflow presented by Polizzi et al [11] , 4DCT images of a QUASAR motion phantom were acquired with both regular and irregular breathing curves. Tumor motion and ITV were analyzed to quantify 4DCT performance.…”
Section: Discussionmentioning
confidence: 99%
“…Two separate groups also recently published a detailed overview of their QA workflow for 4DCT commissioning and periodic QA. In the workflow presented by Polizzi et al [11] , 4DCT images of a QUASAR motion phantom were acquired with both regular and irregular breathing curves. Tumor motion and ITV were analyzed to quantify 4DCT performance.…”
Section: Discussionmentioning
confidence: 99%
“…In general, there is a limitation of breathing speed when scanning a patient with 4DCT. Thus, it is essential to check the specific capabilities and limitations of the CT scanner 24–26 . For example, the maximum value of BPM for the Brilliance Big Bore CT is 60.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is essential to check the specific capabilities and limitations of the CT scanner. [24][25][26] For example, the maximum value of BPM for the Brilliance Big Bore CT is 60.…”
Section: Max Deviation From Eoi (Mm)mentioning
confidence: 99%
“…The authors proposed acceptable volume and amplitude deviation criteria after fine‐tuning acquisition parameters and evaluating results from various phantom studies, with regular and irregular breathing patterns. 50 …”
Section: Opening Statementmentioning
confidence: 99%
“…In recognizing the need to quantify target delineation uncertainties, a more recent study showed that a comprehensive QA of 4DCT could quantify the system's performance. The authors proposed acceptable volume and amplitude deviation criteria after fine‐tuning acquisition parameters and evaluating results from various phantom studies, with regular and irregular breathing patterns 50 …”
Section: Opening Statementmentioning
confidence: 99%